Mechanism Design: How to Implement Social Goals - Maskin, Eric S (American Economic Review, 2008)
The theory of mechanism design can be thought of as the “engineering” side of economic theory. Much theoretical work, of course, focuses on existing economic institutions. The theorist wants to explain or forecast the economic or social outcomes that these institutions generate. But in mechanism design theory the direction of inquiry is reversed. We begin by identifying our desired outcome or social goal. We then ask whether or not an appropriate institution (mechanism) could be designed to attain that goal. If the answer is yes, then we want to know what form that mechanism might take. In this paper, I offer a brief introduction to the part of mechanism design called implementation theory, which, given a social goal, characterizes when we can design a mechanism whose predicted outcomes (i.e., the set of equilibrium outcomes) coincide with the desirable outcomes, according to that goal. I try to keep technicalities to a minimum, and usually confine them to footnotes.